La0.75Sr0.25XO3 (X = Fe, Mn or Cr) with coking tolerance for CH4/H2O reaction: effect of H2S on catalytic performance. Issue 9 (23rd April 2019) - Florea, Mihaela; Somacescu, Simona; Postole, Georgeta; Urdă, Adriana; Neaţu, Florentina; Neaţu, Ştefan; Massin, Laurence; Gélin, Patrick
Abstract : The influence of the B type cation from the ABO3 perovskite formulation La0.75 Sr0.25 XO3 (LSX, where X is Fe, Mn or Cr) on the C and H2 S tolerance and its catalytic activity for the methane/water reaction has been studied. Abstract : The influence of the B type cation from the ABO3 perovskite formulation La0.75 Sr0.25 XO3 (LSX, where X is Fe, Mn or Cr) on the C and H2 S tolerance and its catalytic activity for the methane/water reaction has been studied. The samples were prepared by a simple and cost-efficient citrate method. The exhaustive characterization of the bulk and surface properties of the catalysts has been accomplished by means of complementary methods: nitrogen adsorption–desorption isotherm measurements, XRD, TPR and XPS. Their catalytic properties in CH4 /H2 O reactions (CH4 /H2 O molar ratios of 10 and 1) were studied in the presence and absence of H2 S in order to evaluate their potential use as anode materials in solid oxide fuel cells operated on natural gas. Before addition and upon suppression of H2 S, the activity varied in the following order: LSF > LSM ≫ LSC. This correlates with the oxygen mobility determined by TPR. A strong promoting effect of H2 S on the catalytic activity is observed for LSC, which makes this sample the most active of the series, while H2 S has a weak influence on the other perovskites. The oxygen vacancies and the presence of S 2− were identified as being responsible for the enhanced catalytic activity upon H2 S addition.